The letters of George Santayana. - Santayana, George, 1863-1952 (Works of George Santayana, 2002)
The second of eight books of the correspondence of George Santayana. Since the first selection of George Santayana's letters was published in 1955, shortly after his death, many more letters have been located. The Works of George Santayana, Volume V, brings together a total of more than 3,000 letters. The volume is divided chronologically into eight books of roughly comparable length. Book Two covers Santayana's first decade as a "freelance philosopher," following his resignation from Harvard University and move to Europe. Of particular interest is Santayana's continuing correspondence with the American philosopher Charles Augustus Strong and with his sister Susana Sturgis de Sastre. Also included is correspondence with such notable figures as Bertrand Russell, Robert Seymour Bridges, Horace Kallen, and Logan Pearsall Smith. The correspondence covers Santayana's resignation from Harvard, his time in England during World War I, and comments on his philosophical work during this period.